Satellite Tracking Control System Using Fuzzy PID Controller - Hoi, Tran Van; Truong, Nguyen Xuan; Duong, Bach Gia (VNU Journal of Science: Mathematics - Physics; Vol 31 No 1, 2015)
This paper presents the results of study, design and manufacture of a searching and satellite auto-tracking system used for mobile receiver. This system applies both the traditional proportional integral derivative (PID) control and the fuzzy PID control methods. Firstly, the PID controller was designed by Ziegler-Nichols tuning method to obtain control parameters. Then, a fuzzy controller was applied to tuning online parameters of the PID controller. In order to apply for mobile satellite receiver, the tracking control system has been designed, fabricated on a PCB board. Simulated and experimental results indicate that the system performances obtain from applying the fuzzy PID controller was better than traditional PID controller.    Keywords: Satellite tracking system, step-tracking algorithm, PID controller, Fuzzy controller, satellite communication.